2011
DOI: 10.1111/j.1439-0531.2011.01784.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin‐α Immunohistochemical Expression in Mature and Immature Canine Sertoli and Leydig Cells

Abstract: Formalin-fixed, paraffin-embedded sections from 32 canine pairs of testes were immunohistochemically examined for Inhibin-α (INHα). Samples were subdivided into two groups (group 1, neonates; group 2, puppies and adults) and results statistically compared. Inhibin-α was significantly expressed only in Sertoli cells of neonatal testes, while in Leydig cells it was expressed without significant difference between groups. These results suggest that, in dogs, INHα expression switches from Sertoli to Leydig cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Details of the primary antibodies used, target cells, source, antigen retrieval methods and dilutions are reported in Table 1. All the antibodies employed in the present study were already demonstrated as reactive on targeted canine tissues in previous studies [24,25,26,36,37].…”
Section: Immunohistochemistrymentioning
confidence: 70%
See 4 more Smart Citations
“…Details of the primary antibodies used, target cells, source, antigen retrieval methods and dilutions are reported in Table 1. All the antibodies employed in the present study were already demonstrated as reactive on targeted canine tissues in previous studies [24,25,26,36,37].…”
Section: Immunohistochemistrymentioning
confidence: 70%
“…Since immature aspects can involve both seminiferous tubules structure and spermatogenesis, we used either vimentin (VIM), cytokeratins (CKs), desmin (DES), anti-Müllerian hormone (AMH) and Inhibin-𝛼 (INH) for studying Sertoli cells, and placental alkaline phosphatase (PLAP) to examine germ cells. All these markers have been previously demonstrated in dogs [13,24,[25][26][27][28]. Except for VIM, which is still present in adult life [24], the other markers are specific to the foetal/neonatal period in dogs [24,28].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations